Soil organic carbon and nutrient status in forest and agroforestry lands in tropical region of Nepal - Paudel, Yamuna; Kafle, Gandhiv (Journal of Agriculture and Natural Resources, 2023)
Soil Organic Carbon (SOC) concentration, stock and soil nutrients vary considerably according to land use practices and soil depth. The rationale for studying SOC and nutrient status in Nepal’s tropical forest and agroforestry lands stems from the vulnerability of these soils to degradation, the importance of these systems in carbon sequestration and climate change mitigation, and the need for sustainable land management practices to ensure food security and biodiversity conservation. The objective of the study was to assess the soil organic carbon and nutrient status in Navajagriti community forest, Bharatpur Metropolitan-11 and home gardens (agroforestry) in Kalika Municipality-9 of Chitwan district, Nepal respectively. Soil samples were collected randomly from both land use types. Soil samples were collected from soil depths up to 30 cm at variable depth interval of 0-10 cm and 10-30 cm. The results showed that SOC stock was found higher in agroforestry (25.66 t/ha) than in forest (24.84 t/ha) whereas bulk density was found higher in forest (1.53 g/cmᶾ) than in agroforestry (1.31 g/cmᶾ). The average SOC stock of forest and agroforestry land in 0-10 cm soil depth was found to be 11.40 t/ha and 10.64 t/ha, and those in 10-30 cm soil depth was found to be 13.44 t/ha and 15.02 t/ha respectively. However, both were found non-significant (p<0.05). Likewise, pH (6.5) in agroforestry and 6.29 in forest, total nitrogen in agroforestry (0.216%) and (0.08%) in forest, available phosphorus 37.21 ppm in agroforestry and 7.42 ppm in forest, available potassium in agroforestry 152.22 ppm and 108.8 ppm in forest were found which showed higher nutrient status in agroforestry but these nutrients were not significantly (P>0.05) among both land use type. The carbon-nitrogen ratio was found higher in forest (7.466) than in agroforestry (3.78), with statistical significant difference. The study concluded that SOC concentration, stock, and soil nutrients were highly influenced by management practices like regular tillage, use of organic manure and multistory farming in agroforestry rather than old aged, degraded and unmanaged forest. Hence, forest management applying relevant silvicultural systems based on management objectives and multistory system can improve carbon and nutrient in community forest.